An Attempt at Predicting Postoperative Deep Vein Thrombosis by Preoperative Coagulation Studies in Patients Undergoing Total Hip Replacement - Nilsen, Dennis W T; Jeremic, Miladin; Weisert, Odd K (Thrombosis and Haemostasis, 1980)
Preoperative levels of fibrinogen, factors V, VII, VIII and antithrombin III were measured in 25 consecutive patients undergoing total hip replacement. Deep vein thrombosis (D.V.T.) was detected by fibrinogen-uptake test in 60% of the patients. The preoperative fibrinogen level was significantly higher (p < 0.05), and serum antithrombin III was markedly lower (p ≦ 0.1) in patients with postoperative D.V.T. The quotient of fibrinogen to serum antithrombin III was significantly higher (p < 0.01) in patients with D.V.T. This quotient may serve as an additional parameter to other clinical and laboratory tests in prediction of postoperative D.V.T. following hip surgery.
Keywords: Preoperative coagulation factors; Postoperative thrombosis in hip surgery